VARIATION OF SINTERING TEMPERATURE IN THE SYNTHESIS OF FLUORAPATITE FROM SNAIL SHELLS (Achatina fulica) USING THE SOL-GEL METHOD - Charlena Charlena; Yessie Widya Sari; Wulan Islamia (Tanjungpura University, 2023)
Dental caries can cause porous cavities and even broken teeth, necessitating natural teeth extraction and replacement with implants. Fluorapatite, a dental implant material, can be synthesized from snail shells containing 98% calcium carbonate. This study aims to identify the characteristics of fluorapatite and determine the effect of variations in sintering temperature on the synthesis of fluorapatite made from snail shells using the sol-gel method. Variations of sintering temperature used are 700, 900, and 1100 °C. The results showed that fluorapatite synthesized with the sintering temperature of 900 °C demonstrates the highest crystallinity, according to the diffractogram results, there is an 83% presence of the apatite phase at an angle of 31.8126°, with a crystal size of 79 nm and a particle size of 0.5 µm. Fourier-transform infrared spectroscopy analysis on the sample showed the presence of OH, OH−F, and PO43− functional groups. The sample showed a spongy surface morphology with hexagonal-shaped flowers—a Ca/P molarity ratio 1.67